Evaluation of the clinical effects of dental whitening using two different techniques - Lahoud Salem, Victor (2008)
The purpose of this study was to evaluate clinical effects of dental whitening using two different techniques: the technique used at the dentist and the technique used at home. Ten patients were chosen and divided en two groups, five for each technique. Criteria for evaluation were: color lasting, post operative sensibility, and gums health condition. Results after eight months of clinical evaluation were: 100% of color stability in cases treated with both techniques. Clinical effects of post-operative sensibility were not present in 80% of the cases treated by dentists, while 60% of the cases treated at home presented it. Gum irritation was not present in 100% of the cases treated with both techniques.